2016
DOI: 10.17795/jjcdc-31744
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Knowledge About and Perceived Barriers to Prostate Cancer Screening Among Medical Staff

Abstract: Background: Prostate cancer is the most common cancer among men and the second leading cause of deaths from cancer. Results of previous studies indicate the effectiveness of screening and early detection in reducing mortality from this disease. Objectives: The purpose of this study was to survey the knowledge about prostate cancer and perceived barriers to prostate cancer screening among medical staff of two universities in Ahvaz, Iran. Materials and Methods:This cross-sectional descriptive study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…In this study, the participants' knowledge of prostate cancer and screening behaviors were poor. Consistent with the present study, Barati et al (8), Zahir et al (12), and Akbarizadeh et al (24) showed a low level of awareness among their participants. In this regard, sufficient awareness and knowledge about prostate cancer predict screening behaviors, indicating that with promoting knowledge and awareness, prostate cancer screening behaviors also increase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the participants' knowledge of prostate cancer and screening behaviors were poor. Consistent with the present study, Barati et al (8), Zahir et al (12), and Akbarizadeh et al (24) showed a low level of awareness among their participants. In this regard, sufficient awareness and knowledge about prostate cancer predict screening behaviors, indicating that with promoting knowledge and awareness, prostate cancer screening behaviors also increase.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals are more likely to perform this behavior when they consider themselves at risk for the disease (perceived susceptibility), perceive that the disease has serious consequences (perceived severity), and believe that preventive action has a positive outcome (perceived benefits), that the barriers to that behavior are fewer than its benefits (perceived barriers), and that they are capable of performing health behaviors (self-efficacy). Health Be-lief Model is one of the most accurate and important models used to predict health-related behaviors (11,24,25). The model is underpinned by this theory that individuals' willingness to change their health behavior is primarily due to their health perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with the conceptual framework (health belief model) that participants' knowledge of the disease can affect their perception of the disease [11]. However, this study finding is at variance with the finding of [19] that no significant relationship between knowledge and prostate cancer screening, and it was reported that participants who had poor knowledge about prostate cancer were more likely to screen for prostate cancer compared with those who had good knowledge of prostate cancer [9].…”
Section: Discussionsupporting
confidence: 82%